2021
DOI: 10.3389/fpubh.2021.740800
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Respiratory Diseases Attributable to Ambient Particulate Matter Pollution: Findings From the Global Burden of Disease Study 2019

Abstract: Background: Exposure to ambient particulate matter pollution (APMP) is a global health issue that directly affects the human respiratory system. Thus, we estimated the spatiotemporal trends in the burden of APMP-related respiratory diseases from 1990 to 2019.Methods: Based on the Global Burden of Disease Study 2019, data on the burden of APMP-related respiratory diseases were analyzed by age, sex, cause, and location. Joinpoint regression analysis was used to analyze the temporal trends in the burden of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
(49 reference statements)
0
18
0
Order By: Relevance
“… 29 The authors found that Nepal had the highest death rate from COPD caused by air pollution in 2019; 25.9% of the deaths from COPD were caused by exposure to this risk factor. 29 With rapid urbanisation in Nepal, the use of motorised vehicles has increased from nearly 224 000 in 1990 to 1.3 million in 2012. 30 The high rate of deaths in Nepal might be because of failure to effectively regulate air pollutants and ineffective implementation of air quality control measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 The authors found that Nepal had the highest death rate from COPD caused by air pollution in 2019; 25.9% of the deaths from COPD were caused by exposure to this risk factor. 29 With rapid urbanisation in Nepal, the use of motorised vehicles has increased from nearly 224 000 in 1990 to 1.3 million in 2012. 30 The high rate of deaths in Nepal might be because of failure to effectively regulate air pollutants and ineffective implementation of air quality control measures.…”
Section: Discussionmentioning
confidence: 99%
“…The highest age standardised death rate in 2019 was found in Nepal, with 182.5 deaths per 100 000 population. A recent study used data from the Global Burden of Disease 2019 study to evaluate the burden of respiratory diseases attributable to pollution from ambient particular matter 29. The authors found that Nepal had the highest death rate from COPD caused by air pollution in 2019; 25.9% of the deaths from COPD were caused by exposure to this risk factor 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ongoing pandemic COVID-19, this disease is considered to be an underlying disease that easily leads to an increased risk of hospitalization and death [ 4 ]. Therefore, the high mortality and morbidity of COPD pose a great danger to human health and become a global public health challenge [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factors of COPD development can be attributed to smoking and air pollution [ 5 ], but the exact pathogenesis is still unclear. It is generally believed that COPD develops chronically in the respiratory system due to the release of inflammatory mediators resulting in abnormal immune functions.…”
Section: Introductionmentioning
confidence: 99%